ERROR ANALYSIS ON RECOUNT TEXTS PRODUCED BY TWELFTH GRADERS OF SMAN 3 MALANG - WIBISONO, KAMALA (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords: Error Analysis, error, narrative paragraph, types of error English as an international language has an important role to develop science and technology. Many countries in the world use English as a medium of communication among people in different countries and also of writing many kinds of books in which those are spread in different countries. In Indonesia there are many kinds of foreign books written in English, they claim Indonesian students to be able to learn and to use English in schools or in society in order that the books they read can be applied in various fields so that the development of science and technologies in Indonesia can be obtained. Although English is a foreign language, Indonesian students, from elementary up to university levels should learn English. In the process of learning, Indonesian students surely make errors. It is understandable since the rule of Bahasa Indonesia and English is different.This research has aims: (1) to identify the types of errors and (2) to find the most frequently error in the recount text produced by the twelfth graders SMA Negeri 3 Malang.This research is designed by using descriptive qualitative research and document analysis to answer the problems of the study. The data were collected from the twenty recount texts produced by the twelfth graders students of bilingual class of SMA Negeri 3 Malang. In collecting the data, the researcher asked the students to write a paragraph about 150 until 200 words with a topic. The researcher analyzed the data by using the theories from Dulay, Burt, and Krashen (1982) about surface strategy taxonomy.The results of this research are found that the students did errors when they wrote a narrative writing. Those errors are omission, addition, misformation, and misordering. Omission were divided into some parts, omission of preposition, omission of „be‟,plural marker,article and subject. Then, addition were divided into two types, addition of „be‟ and addition of verb. Misformation also divided into two types, misformation of „be‟ and misformation of verb. The last is misordering.The researcher suggests to the next writers who want to conduct the similar research to use the different object and analyze the errors with other theories. Another suggestion is to use the same theory but with the different object like using a textbook or an article for the data.